Analisis Elemen Gamifikasi dan Micro-interactions pada Aplikasi Duolingo: Tinjauan Literatur Sistematis - Yasmin Yasmin; Hifni Fadhilah; Muhamad Fikri; Miftahul Huda (Journal of Science, Technology, and Innovation, 2025)
Low user engagement and long-term retention remained key challenges in mobile learning applications despite advancements in instructional content and functionality. This study aimed to examine the role of gamification elements and micro-interactions in enhancing user engagement in mobile-based language learning applications, with a focus on Duolingo and similar platforms. A Systematic Literature Review method was employed, following the stages of identification, screening, eligibility assessment, and inclusion. Literature searches were conducted through Google Scholar and ResearchGate, covering studies published between 2020 and 2025. Ten articles that met the inclusion criteria were analyzed using qualitative synthesis. The results indicated that gamification elements such as points, badges, leaderboards, and streaks contributed to increased learner motivation and consistent application use. In addition, micro-interactions supported user engagement by improving system clarity, interaction comfort, and feedback responsiveness. This study concluded that a balanced integration of gamification and micro-interactions was essential for developing sustainable and effective mobile learning applications.